Prevalence of chronic pelvic pain and primary dysmenorrhea in women of reproductive age in Ecuador - Carmen Yolanda de Las Mercedes Villa Rosero; Suleimy Cristina Mazin; Antonio Alberto Nogueira; José Antonio Vargas-Costales; Julio Cesar Rosa-; Francisco José Candido-; Omero Benedicto Poli-Neto (BMC, 2022)
Abstract Background Chronic pelvic pain (CPP) and primary dysmenorrhoea are debilitating conditions that can impair the quality of life of affected women. These conditions are frequently neglected, delaying proper diagnosis and healthcare provision. This study aimed to estimate the prevalence of CPP and primary dysmenorrhoea in Ecuador and identify potential variables associated with their occurrence. Methods We conducted a cross-sectional survey in an urban neighbourhood of Quito, the capital of Ecuador. A total of 2397 participants of 14-49 years of age were included. The data were collected through questionnaires administered by trained interviewers.The crude and adjusted prevalence ratios were calculated using a log-binomial regression model. The correlation between pain intensity catastrophising of symptoms were statistically analysed. Results The prevalence of CPP and primary dysmenorrhoea was 9.8% and 8.9%, respectively. Irritative urinary symptoms, primary dysmenorrhoea, and underlying mental disorders were associated with CPP, while smoking, irritable bowel syndrome, sleep disturbance, dyspareunia, and mental disorders were associated with primary dysmenorrhoea. Conclusions The prevalence of CPP and primary dysmenorrhoea in Ecuador was similar to that in other Latin American countries. Primary dysmenorrhoea is a risk factor of CPP, and less than a quarter of women are undergoing treatment for the condition. Our findings reinforce the importance of healthcare interventions in anticipating the diagnosis of these conditions in women of reproductive age.